Respuesta :
Answer:
Add [tex]-x^2+2xy[/tex]
Step-by-step explanation:
The polynomial [tex]x^2+y^2-2xy+1[/tex] can be added to eliminate the x terms by adding the additive inverse. We add [tex]-x^2+2xy[/tex] which has the inverse sign value of the polynomial terms.
[tex](x^2+y^2-2xy+1)+(-x^2+2xy)[/tex]
[tex]x^2-x^2+y^2-2xy+2xy+1[/tex]
When we simplify, this leaves [tex]y^2+1[/tex] without an x term.
Answer:
-x^2+2xy
Step-by-step explanation:
x^2 + y^2 -2xy + 1 +something = y^2 +1
This will get rid of the x and x^2 terms
Subtract y^2 from each side
x^2 + y^2 -y^2 -2xy + 1 +something = y^2-y^2 +1
x^2 -2xy+1 +something = 1
Subtract 1 from each side
x^2 -2xy+1 -1+something = 1-1
x^2 -2xy+something = 0
Subtract x^2 from each side
x^2 -x^2 -2xy+something = 0-x^2
-2xy+something = -x^2
Add 2xy to each side
2xy -2xy+something = -x^2+2xy
something = -x^2+2xy
We need to add -x^2+2xy
Remember a binomial is 2 terms